Liver transplantation for hepatitis B liver disease and concomitant hepatocellular carcinoma in the United States With hepatitis B immunoglobulin and nucleoside/nucleotide analogues. Issue 9 (28th August 2013) - Campsen, Jeffrey; Zimmerman, Michael; Trotter, James; Hong, Johnny; Freise, Chris; Brown, Robert; Cameron, Andrew; Ghobrial, Mark; Kam, Igal; Busuttil, Ronald; Saab, Sammy; Holt, Curtis; et al.
<x xml:space="preserve">Abstract</x> Reinfection with hepatitis B virus (HBV) after liver transplantation (LT) may favor the recurrence of hepatocellular carcinoma (HCC), and combination therapy with hepatitis B immunoglobulin (HBIG) and nucleoside/nucleotide analogues may reduce HBV recurrence after LT. To test associations between HBV, HCC, and survival, we performed a retrospective chart review of patients undergoing LT for HBV between January 1985 and December 2010 at 7 US transplant centers. After we divided the patients into 3 eras based on evolving strategies in antiviral therapy (1985‐1994, 1995‐2004, and 2005‐2010), we reviewed 16 variables to determine whether there were associations between survival and HCC recurrence. Seven hundred thirty‐eight patients underwent transplantation for HBV, and 354 (48.0%) had concomitant HCC, which recurred in 58 patients (16.4%). Three‐year survival was much better in era 3 versus era 1 (87% versus 40%, P = 0.001), and the incidence of HCC recurrence was lower (12% versus 29%, P = 0.009). The lungs were the most frequent first site of HCC recurrence, and they were followed by the liver. A multivariate analysis showed that HBV reinfection, HCC recurrence, and HBIG use were associated with worse survival (P < 0.001, P < 0.001, and P = 0.002, respectively); HCC recurrence and stage 3 HCC, among other factors, were associated with HBV reinfection (P < 0.001 and P = 0.004); and stage 3 HCC, vascular invasion of the explanted tumor, and post‐LT chemotherapy were associated with HCC recurrence (P = 0.008, P < 0.001, and P < 0.001, respectively). Patients with HBV reinfection were 3.6 times more likely than patients without HBV to have HCC recurrence. These data suggest further study of attempts at LT for patients with HBV and HCC beyond the Milan criteria if their HBV is aggressively and successfully treated. Liver Transpl 19:1020‐1029, 2013. © 2013 AASLD.